Q: X2 - x - 6 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-x2 = x - 6 x2 + x - 6 = 0 (x - 2)(x + 3) = 0 x ∈ {-3, 2}

(x + 6)(x - 6)

x2- 7x + 6 = 0 factor, (x-6)(x-1) = 0 x = 6 x = 1

x2 + x - 30 = (x + 6)(x - 5)

Strictly speaking, it is a quadratic equation in x. x2 + x = 6 => x2 + x - 6 = 0 => (x+3)*(x-2) = 0 => x = -3 or x = 2

Related questions

-x2 = x - 6 x2 + x - 6 = 0 (x - 2)(x + 3) = 0 x ∈ {-3, 2}

(x + 6)(x - 6)

x2- 7x + 6 = 0 factor, (x-6)(x-1) = 0 x = 6 x = 1

x2+x-6=0 * * * * * Perhaps the solution you are looking for is: x2 + x - 6 = (x - 2)(x + 3) = 0; whence, x = 2 or -3.

x2 - 2x - 5 = 0 x2 - 2x + 1 = 6 (x - 1)2 = 6 x - 1 = ± √6 x = 1 ± √6

x2 + x - 30 = (x + 6)(x - 5)

Strictly speaking, it is a quadratic equation in x. x2 + x = 6 => x2 + x - 6 = 0 => (x+3)*(x-2) = 0 => x = -3 or x = 2

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}

x2 + 5x =6 x2+5x -6 = 0 (x+6)(x-1) = 0 x+ 6 = 0 x = -6 x-1 = 0 x = 1

x = -2 and x = 6

-5, -6